The crystal structure of camerolaite and structural variation in the cyanotrichite family of merotypes. (December 2014) - Mills, S. J.; Christy, A. G.; Schnyder, C.; Favreau, G.; Price, J. R.
Abstract: We present Raman data for camerolaite, cyanotrichite and carbonatecyanotrichite, and using synchrotron single-crystal X-ray diffraction have solved the structure of camerolaite from the Tistoulet Mine, Padern, Aude Department, France. Camerolaite crystallizes in space group P 1 with the unit-cell parameters: a = 6.3310(13) Å, b = 2.9130(6) Å, c = 10.727(2) Å, α = 93.77(3)°, β = 96.34(3)°, γ =79.03(3)º, V = 192.82(7) Å 3 and Z = ⅓, with respect to the ideal formula from the refinement, Cu6 Al3 (OH)18 (H2 O)2 [Sb(OH)6 ](SO4 ). The crystal structure was solved to R 1 = 0.0890 for all 1875 observed reflections [ F o > 4σFo ] and 0.0946 for all 2019 unique reflections. The P cell has been transformed into a C -centred cell that aids comparison with that of the structurally related khaidarkanite bya C = 2a P –b P, giving parameters a = 12.441(3), b = 2.9130(6), c = 10.727(2) Å, α = 93.77(3), β = 95.57(3), γ = 92.32(3)º and Z = ⅔ in C1. Edge-sharing octahedral ribbons Cu2 Al(O, OH, H2 O)8 form hydrogen-bonded layers || (001), as in khaidarkanite. The partially occupied interlayer Sb and S sites of the average structure are in octahedral and tetrahedral coordination by oxygen, respectively. They cannot be occupied simultaneously, which leads to regular alternation of [Sb(OH)6 ] – and SO4 2– groups in rods ||y, resulting in local tripling of the periodicity alongy for the Sb(OH)6 –SO4 rods. Thus, camerolaite has a 'host–guest' structure in which an invariant host module (layers of Cu–Al ribbons) has embedded rod-like guest modules with a longer periodicity. Coupling between the phases of these rods is only short-range, resulting in diffuse X-ray scattering rather than sharp superstructure reflections. Similar disorder is known for parnauite, and is deduced for other members of the cyanotrichite group (cyanotrichite, carbonatecyanotrichite and khaidarkanite). Group members all share the Cu–Al ribbon module but have interlayer rods of different compositions and topologies; thus, they form a merotypic family. The low symmetry of the camerolaite average structure suggests other possibilities for structure variation in the group, which are discussed.